2013
DOI: 10.1002/bjs.8990
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary perioperative care strategies

Abstract: Background: Historically, the preoperative and postoperative care of patients with gastrointestinal cancer was provided by surgeons. Contemporary perioperative care is a truly multidisciplinary endeavour with implications for cancer-specific outcomes.Methods: A literature review was performed querying PubMed and the Cochrane Library for articles published between 1966 to 2012 on specific perioperative interventions with the potential to improve the outcomes of surgical oncology patients. Keywords used were: fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
9

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 237 publications
(267 reference statements)
1
18
0
9
Order By: Relevance
“…Major abdominal surgery represents a significant physiological stress and is followed by a period of disability, traditionally termed convalescence. Surgical innovations are often advocated on the basis that they shorten this period of disability and therefore improve recovery. However, accurate measurement of the construct of surgical recovery has been hampered by lack of an accepted definition and lack of instruments validated in this context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Major abdominal surgery represents a significant physiological stress and is followed by a period of disability, traditionally termed convalescence. Surgical innovations are often advocated on the basis that they shorten this period of disability and therefore improve recovery. However, accurate measurement of the construct of surgical recovery has been hampered by lack of an accepted definition and lack of instruments validated in this context.…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced recovery pathways (ERPs) are multidisciplinary clinical care pathways that integrate evidence‐based interventions in all perioperative phases to attenuate the surgical stress response and accelerate recovery in patients undergoing major abdominal surgery. The challenge in evaluating ERPs lies in determining how best to measure the effect of the pathway on the stress response and recovery.…”
Section: Introductionmentioning
confidence: 99%
“…On the contrary, the inverse correlation between transfusions and long-term survival which has been previously shown was not confirmed. However, most studies [24]- [26] have shown that perioperative surgical stress cause immunosuppression, which could be exacerbated by concomitant transfusions. This condition could promote tumor relapse and metastatic process and could be explained by the infusion of an incompatible MHC antigen.…”
Section: Discussionmentioning
confidence: 99%
“…Other caused by factor extrinsic which are the distance between patient"s body and position and also the instruments being used to maintain patient"s position during surgery, friction and also haemodynamic changes. 16 Risk for infection is another nursing diagnosis. Other risk factors for infection are tissue location, contamination degree that will influence surgery infection, nutrition state, radiotherapy before surgery, renal failure, ventilator requirement, using colostomy bag, massive blood transfusion, and hypothermia during surgery.…”
Section: Diagnoses In Intra Operative Statementioning
confidence: 99%